Optimal Delivery of Pain Management in Schwannomatosis: A Literature Review - Hino U; Tamura R; Toda M (Therapeutics and Clinical Risk Management)
Utaro Hino,1 Ryota Tamura,2 Masahiro Toda2 1Department of Neurosurgery, Saiseikai Yokohamashi Tobu Hospital, Kanagawa, Japan; 2Department of Neurosurgery, Keio University School of Medicine, Tokyo, JapanCorrespondence: Ryota Tamura, Department of Neurosurgery, Keio University School of Medicine, 35 Shinanomachi, Shinjuku-ku, Tokyo, 160-8582, Japan, Email moltobello-r-610@keio.jpAbstract: Non-NF2 schwannomatosis is a rare syndrome characterized by multiple benign schwannomas that primarily affect nerve sheaths, with chronic, treatment-resistant pain as the most common symptom. No protocol has been established for pain management, and pharmacotherapies, including molecular target therapies, are being evaluated. Neuromodulation therapies such as scrambler therapy and surgical options are also employed; however, surgery may lead to persistent or recurrent pain caused by nerve damage or tumor recurrence. The lack of accurate animal models hampers understanding of pain mechanisms and tumor development, necessitating further basic research and clinical trials to improve treatment strategies.Keywords: schwannomatosis, pain, surgery, medication, neuromodulation